AN EXAMINATION OF THE RELATIONSHIP BETWEEN SUPPLY CHAIN MANAGEMENT PRACTICES AND BUSINESS PERFORMANCE: A CASE ANALYSIS OF A PASSENGER RAIL COMPANY - Fourie, Cornelius Jacobus; Chimusoro, Oliver (The South African Journal of Industrial Engineering, 2018)
The lack of maintenance engineering performance is one of the main causes of poor service delivery. In a passenger rail company, maintenance engineering performance is measured using several parameters, which include the ability of the organisation to upgrade and replace its fleet, the availability of spares, skills availability, information flow, and information technology. The aim of this study was to investigate the situation in a passenger rail company in South Africa in order to determine whether its supply chain management practices would influence business performance and, in this case, maintenance engineering performance. After a chi-square test was done, the results showed that there was a positive influence by supply chain management practices on business performance.